2014
DOI: 10.1111/joor.12145
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dentine hypersensitivity in Chinese rural adults with dental fluorosis

Abstract: Summary The aim of this study was to estimate the prevalence of dentine hypersensitivity (DH) among residents of rural China with dental fluorosis aged 30–69 years. A village located in northern China in which dental fluorosis was common was selected. Some 1250 residents with fluorosis ranging in age from 30 to 69 years completed a structured questionnaire and underwent clinical examination. Diagnosis of DH was based on the combination of the subject's self‐evaluation and clinical examination. Dental fluorosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…Like many studies, the most common initiating factor of DS in this study was cold stimuli . Acidic or sour foods were reported by 11.6% of patients as initiators of DS symptoms in the Trinidadian study.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Like many studies, the most common initiating factor of DS in this study was cold stimuli . Acidic or sour foods were reported by 11.6% of patients as initiators of DS symptoms in the Trinidadian study.…”
Section: Discussionsupporting
confidence: 50%
“…The most common initiating factor in these DS studies (Table ) has been cold stimuli . Hard and acidic foods were significantly associated with DS among Thai dental patients .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The children in our study were the most affected by severe EF, with pitting and loss of permanent teeth, and increased tooth sensitivity were widely observed among the young children enrolled in the study. Such effects and increased risk of tooth decay have previously been documented in studies from other locations (Levy 2003; Burt and Eklund, 1999; Wondwossen et al, 2004; Mine et al, 2011; Zhang et al, 2014), and EF has also been linked to psychological and social impacts due to stigma arising from the brownish discoloration of individuals' teeth (Wondwossen et al, 2006). Consistent with these impacts, many individuals that participated in the study reported an inability to chew hard foods (loss of dental function) from a young age, which harms the overall quality of life.…”
Section: Discussionmentioning
confidence: 80%
“…Dentine hypersensitivity (DH) is a common oral complaint characterized by 'short, sharp pain arising from exposed dentin in response to stimuli typically thermal, evaporative, tactile, osmotic, or chemical and which cannot be ascribed to any other form of dental defect or pathology' [2]. It is a highly prevalent oral condition, affecting 9.7-34.1 % of Chinese people [3][4][5]. This oral disorder not only affects patients' physical health, but also affects their social functions and psycho-social well-being [6][7][8].…”
Section: Introductionmentioning
confidence: 99%